Household level fuelwood use and carbon dioxide emissions in Delanta district, Northeastern Ethiopia - Sintayehu Eshetu, Abebaw (Frontiers in Environmental Science, 2025)
IntroductionEthiopian rural households primarily rely on fuelwood as their main energy Q7 source, yet the country lacks precise data on fuelwood harvesting and its economic significance. Consequently, there is limited understanding of CO2 emissions resulting from fuelwood use.MethodsThis study aimed to estimate the annual amount of fuelwood collected and the associated CO2 and carbon (C) emissions. Using simple random sampling for household selection, data were analyzed with Excel and Stata.ResultsThe results reveal that fuelwood dependency is a major driver of deforestation and CO2 emissions, with households consuming approximately 2,725 kg of firewood and 26 kg of charcoal annually. Each household also extracts an average of 3,909.3 kg of firewood and 516.5 kg of charcoal annually for sale. Among sampled households, fuelwood constitutes 904,261 kg of energy, with 51% used for household consumption and 96% allocated for income generation. The inefficient burning of this fuel results in significant emissions, adding 974,000 kg of CO2 or 265,600 kg of carbon annually to the household carbon footprint. On average, each household emits 7,740 kg of CO2 and 1,960 kg of carbon per year.DiscussionThe study emphasizes that, while fuelwood plays a critical role in household energy and income, its unsustainable use accelerates emissions and deforestation. To mitigate these effects, the adoption of alternative energy sources like electricity and forest conservation through local plantations is essential for climate resilience.